AMANAT PADA KUMPULAN CERITA RAKYAT KERINCI SAKUNUNG-SAKUNUNG NINAU DI DESA PULAU TENGAH KABUPATEN KERINCI - Sainil Amral; Nur Azlin (Universitas Batanghari, 2020)
The purpose of this research to describe trusteeship in the folklores of Kerinci Sakunung-sakunung ninau in Desa Pulau Tengah Kabupaten Kerinci which consists of two aspects, namely implied trusteeship and express trusteeship. The data in this research is primary data in a form of expressions in the folklores of Kerinci Sakunung-sakunung ninau in Desa Pulau Tengah Kabupaten Kerinci. The source of the data is the folklores of Kerinci Sakunung-sakunung ninau in Desa Pulau Tengah Kabupaten Kerinci. This research is qualitative descriptive. Based on the collection of the data, transcribing the data, and analyzing the data, the trusteeship in the folklores of Kerinci Sakunung-sakunung ninau in Desa Pulau Tengah Kabupaten Kerinci can be understood. Moreover the researcher interprets logically and makes conclusions towards findings. Based on data tabulation, two points of view are occured. They are implied trusteeship and express trusteeship. The most dominant type occured is express trusteeship while the least is implied trusteeship. There are 41 expressions found; 20 expressions of implied trusteeship and 21 expressions of express trusteeship. Thus it can be concluded that both implied and express trusteeship occured in the folklores of Kerinci Sakunung-sakunung ninau.